2004
DOI: 10.1177/002214650404500106
|View full text |Cite
|
Sign up to set email alerts
|

Marital Status, Marital Transitions, and Health: A Gendered Life Course Perspective

Abstract: We work from a life course perspective to assess the impact of marital status and marital transitions on subsequent changes in the self-assessed physical health of men and women. Our results suggest three central conclusions regarding the association of marital status and marital transitions with self-assessed health. First, marital status differences in health appear to reflect the strains of marital dissolution more than they reflect any benefits of marriage. Second, the strains of marital dissolution underm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
523
4
11

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 572 publications
(568 citation statements)
references
References 36 publications
30
523
4
11
Order By: Relevance
“…In addition, diabetes status per se was associated with poor quality of life and disability, as were socio-economic status (low education), being in a low wealth quintile, having a poor employment history, marital status (not being in a partnership), lifestyle habits (low physical activity, history of alcohol use) and co-morbid conditions. In accordance with previous studies, we found that having  diabetes [2022], having lower formal education levels [23–25], being in a low socioeconomic group [26,27], not being in a marital relationship [28,29] and not having worked [30,31] were significantly associated with poor quality of life and a high level of disability, but unlike findings in other studies [3235], being older and being female were not associated with a high level of disability 20222325 26,27 28,29]30,31 3235 The differences in findings in this study compared to others may relate to the use of different instruments to assess the quality of life and disability, as well as the use of diabetes-specific and generic measures across studies.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, diabetes status per se was associated with poor quality of life and disability, as were socio-economic status (low education), being in a low wealth quintile, having a poor employment history, marital status (not being in a partnership), lifestyle habits (low physical activity, history of alcohol use) and co-morbid conditions. In accordance with previous studies, we found that having  diabetes [2022], having lower formal education levels [23–25], being in a low socioeconomic group [26,27], not being in a marital relationship [28,29] and not having worked [30,31] were significantly associated with poor quality of life and a high level of disability, but unlike findings in other studies [3235], being older and being female were not associated with a high level of disability 20222325 26,27 28,29]30,31 3235 The differences in findings in this study compared to others may relate to the use of different instruments to assess the quality of life and disability, as well as the use of diabetes-specific and generic measures across studies.…”
Section: Discussionsupporting
confidence: 92%
“…However, the existing longitudinal studies indicate, like the cross-sectional studies, that marriage is associated with higher life satisfaction (39,43) and greater affective happiness (44). Evidence moreover suggests that marriage is associated with better mental health, physical health, and longevity, even controlling for baseline health (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55). Concerning character and virtue, although understudied and current outcome measures are inadequate, there is longitudinal evidence that marriage is associated with higher level of personal growth (44), and with a reduction in crime for those at high risk (56).…”
Section: Prominent Pathways To Human Flourishingmentioning
confidence: 99%
“…Cohabiting men and especially married men have more contacts with their family (Eggebeen, 2005), are more strongly attached to the labour force (Rindfuss and VandenHeuvel, 1990) and have higher levels of physical health and psychological well-being (Coombs, 1991;Waite, 1995;Akerlof, 1998;Brown, 2000;Brown, Bulanda, and Lee, 2005;Woo and Raley, 2005). Furthermore, experiencing dissolution of a partnership is related to men's psychological, social, health, and economic activities and well-being as well; divorced men have less contact with their family (Gerstel, 1988), exhibit less healthy behaviour (Williams and Umberson, 2004), are less committed to their occupational careers (Kalmijn, 2005), and are more distressed (Wallerstein and Blakeslee, 1990;Booth and Amato, 1991). To find out whether differences between childless men and fathers are attributable to partnership history, we explicitly take partnership history into account in our analyses.…”
Section: Partnership Historymentioning
confidence: 99%